The oligopolistic behavior of Kazakh and Russian wheat exporters in the South Caucasus: Evidence from a residual demand elasticity analysis - Gulmira Gafarova; Oleksandr Perekhozhuk; Thomas Glauben (Journal of Industry, Competition and Trade, 2023)
This study looks at whether Kazakh and Russian wheat exporters leverage their dominant share of the wheat markets in the South Caucasus to exercise market power. We apply a three-stage estimation for systems of simultaneous equations and Zellner's seemingly unrelated regression to analyze residual demand elasticity. The results of both estimations provide empirical evidence of Russian market power in the wheat markets of the South Caucasus but no evidence of a Kazakh oligopoly. Russian exporters possess greater market power in Armenia than in Georgia. Market power depends on the presence of competitors in the destination market. The results show that Kazakh exporters restrict the market powers of Russian exporters in the Azerbaijani wheat market, while Russian exporters constrain the market power of Kazakh exporters in the Azerbaijani and Georgian wheat markets. Ukrainian wheat exporters are able to intervene in the market powers of Russian exporters in Azerbaijan and Georgia, while they restrict Kazakh oligopoly in the Georgian market. Some export restrictions imposed by wheat exporting countries significantly affected competition in wheat importing countries. Russia's ongoing war against Ukraine and the blockade of Ukrainian ports on the Sea of Azov and the Black Sea are restricting wheat trade, severely damaging Ukraine's competitiveness and export potential, and reducing food security in the South Caucasus, the Middle East, and North Africa.
Keywords: L13; Q11; Q17; Q18; 330; Black sea wheat trade; imperfect competition; market power; residual demand elasticity; wheat export restrictions; South Caucasus; Russia; Kazakhstan; Ukraine